PUTH Grading System for Urinary Tumor With Supradiaphragmatic Tumor Thrombus: Different Surgical Techniques for Different Tumor Characteristics - Liu, Zhuo; Li, Yuxuan; Zhang, Yu; Zhao, Xun; Ge, Liyuan; Tang, Shiying; Hong, Peng; Zhang, Shudong; Tian, Xiaojun; Wang, Shumin; Liu, Cheng; Zhang, Hongxian; et al. (Frontiers in Oncology, 2022)
Purpose: To explore the different treatment strategies for urinary tumors with Mayo IV thrombus. Materials and Methods: We retrospectively analyzed the patients with Mayo IV thrombus in Peking University Third Hospital from January 2014 to April 2021. We used the Peking University Third Hospital (PUTH) grading system to classify urinary tumors with supradiaphragmatic thrombus. PUTH-A referred to the filled thrombus whose tip just reached above the diaphragm, or the thrombus entering the right atrium (< 2cm). PUTH-B referred to the filled thrombus entering the right atrium (> 2cm), or the thrombus invading the wall of the inferior pericardial vena cava. Detailed techniques were described for various scenarios. Clinicopathological data and perioperative outcomes were reported. Group difference statistical analysis was performed. Results: A total of 29 cases of urinary tumors with supradiaphragmatic IVC thrombus (Mayo grade IV) underwent treatment were enrolled in this study. 21 patients in the PUTH-A group received the open approach without sternotomy and cardiopulmonary bypass. Eight patients in the PUTH-B group received open thoracotomy assisted by cardiopulmonary bypass. No intraoperative death occurred. After 56 months of follow-up, 46.2% (12 of 26) patients died of all causes. Estimated 1-year, 2-year, and 3-year overall survival were 72.0% (95% CI, 54.4%-89.6%), 58.2% (95% CI, 38.0%-78.4%), and 52.4% (95% CI, 31.2%-73.6%), respectively. Conclusions: We introduced the PUTH grading system for the characteristics of urinary tumors with supradiaphragmatic tumor thrombus, and selected different surgical techniques according to different classifications. This grading system was relatively feasible and effective.